Education and Training Revolution : A Review on AR, VR, and IoT Integration in Educational Perspective - Vimala, Govindaraju; Dhanabalan, Thangam (CRC Press (Taylor & Francis Group), 2025)
Augmented reality (AR), virtual reality (VR), and the Internet of Things (IoT) have changed the way learning. AR, VR, and IoT are a few of the most important in training and education. AR and VR give students a variety of interactive experiences that can help them understand and retain complex concepts. These technologies allow students to experiment with real life scenarios, visualize ideas, and do virtual research. IoT combines physical and digital platforms to create a smart learning environment that enables real time data collection, analysis, and feedback. Interdependence not only facilitates adaptive assessments and effective classroom management but also facilitates personalized educational programs. Chapter presents case studies and empirical research that demonstrate the efficacy of AR, VR, and IoT across a broad spectrum of educational levels, including primary, secondary, and professional education, as well as training and professional programs. It also addresses affordability, accessibility, and the need for teacher training to incorporate new technologies into the curriculum. The chapter highlights the potential of AR, VR, and IoT in fostering inclusive, innovative, and dynamic learning environments, while also exploring future prospects through current trends and IoT.